Sistem Informasi Pelayanan Izin Penelitian pada Badan Kesbangpol Aceh (Yayasan Kawanad, 2022)
The purpose of this research is to assist the Aceh Kesbangpol in the research licensing service process to computerize the current system so that it can analyze and assist database processing activities at an even better level of effectiveness and efficiency, so that it is expected to be able to; designing and building a web-based research permit service information system at the Aceh Kesbangpol Agency, implementing a web-based research permit service information system with an integrated SMS Gateway, and producing more effective and efficient research permit service reports. The method used in this design is the waterfall method. Based on the results of research on the research permit service information system at the Aceh Kesbangpol Agency based on the web-based integrated SMS Gateway that has been carried out by the author, several conclusions can be drawn, namely; This research was successful in creating a web-based integrated information system research permission service with SMS Gateway. SMS Gateways.